A rebuttal of recent arguments for Maragha influence on Copernicus - Viktor Blåsjö (Studia Historiae Scientiarum)
I reply to recent arguments by Peter Barker & Tofigh Heidarzadeh, Arun Bala, and F. Jamil Ragep claiming that certain aspects Copernicus’s astronomical models where influenced by late Islamic authors connected with the Maragha school. In particular, I argue that: the deleted passage in De revolutionibus that allegedly references unspecified previous authors on the Tusi couple actually refers to a simple harmonic motion, and not the Tusi couple; the arguments based on lettering and other conventions used in Copernicus’s figure for the Tusi couple have no evidentiary merit whatever; alleged indications that Nicole Oresme was aware of the Tusi couple are much more naturally explained on other grounds; plausibility considerations regarding the status of Arabic astronomy and norms regarding novelty claims weight against the influence thesis, not for it.